Aquifers Matrix and Fluids - Salik Javaid, Muhammad; Ali Khan, Shaukat (IntechOpen, 2018)
The rock matrix and the fluids contained therein define the aquifer as a whole, the custodian of continuity of life on this planet Earth. Its sustainable development, equitable utilization, quality maintenance, and balanced discharge and recharge are the essential elements to ensure that the next generation receives the resource baton passed on by the current generation. Spanning across the political and regional frontiers, transboundary aquifers have the potential to provide a uniting platform to the participatory nations. The common good of water can be enhanced by synergized research, data and knowledge sharing, joint development ventures, and hazard mitigation. Covering the multifarious facets of aquifers, this book will form an essential and interesting reading for all stakeholders?researchers, engineers, academia, intelligentsia, and the common consumer.